Exploring the Impact of Curing Techniques on the Compressive Strength of Concrete Structures: A Comprehensive Investigation - Bhattarai, Y.; Chapagain, P.; Panthi, S.; Shrestha, S. P. (Journal of Lumbini Engineering College, 2024)
This research investigates the influence of various curing methods on the compressive strength of plain concrete, exploring techniques such as water ponding, jute curing, plastic bag curing, dry curing, and geo-textile curing. Emphasizing both early and long-term concrete strength enhancement, the study identifies water ponding and geo-textile curing as the most promising for high early strength, while jute curing and plastic bag curing exhibit moderate performance, with dry curing ranking as the least effective. Incorporating insights from industry professionals through a structured questionnaire, the research underscores the collective awareness of the pivotal role of proper curing practices in concrete strength and durability. The study recommends further exploration into the influence of varying slump values and alternative curing methods, considering diverse environmental conditions, with the potential to optimize curing practices for robust and durable concrete structures. In conclusion, this research highlights the critical importance of correct curing practices for ensuring concrete structures’ strength and longevity, offering practical implications for the construction industry and civil engineering.